 # RD Sharma Solutions Class 11 Trigonometric Ratios Of Compound Angles

## RD Sharma Solutions Class 11 Chapter 7

The RD Sharma books are based on the latest CBSE syllabus according to the CCE guidelines. The RD Sharma class 11 solutions for the chapter Trigonometric Ratios of Compound Angles is given here.

A compound angle is an angle made up of the algebraic sum of two or more angles. The formulas for the trigonometric ratios of compound angles are given below.

• sin(P – Q) = sin P cos Q – cos P sin Q
• sin(P + Q) = sin P cos Q + co P sinQ
• cos(P – Q) = cos P cos Q + sin P sin Q
• cos(P + Q) = cos P cos Q – sin P sin Q
• tan(P – Q) = tan P – tan Q/ 1 + tan P tan Q
• tan(P + Q) = tan P + tan Q/ 1 – tan P tan Q
• sin(P + Q) sin(P – Q) = sin 2P – sin 2Q = cos 2Q – cos 2P
• cos(P + Q) = cos(P – Q) = cos 2P – sin 2P – sin 2Q = cos 2Q – sin 2P

The detailed RD Sharma solutions for class 11 Chapter 7: Trigonometric Ratios of Compound Angles is given in the table below. The RD Sharma solutions are comprehensive and easy to understand.

 Chapter 7  Trigonometric Ratios of Compound Angles Trigonometric Ratios of Compound Angles Exercise 7.1 Trigonometric Ratios of Compound Angles Exercise 7.2